PENGARUH MODEL PEMBELAJARAN CONCEPT ATTAINMENT TERHADAP AKTIVITAS DAN HASIL BELAJAR MAHASISWA PADA MATA KULIAH EPIDEMIOLOGI MATERI MORBIDITY MEASUREMENT - aldila wanda (Universitas Cokroaminoto Palopo, 2022)
This study aims to determine the activities and learning outcomes of students before and after the application of the concept attainment learning model in the epidemiology subject on morbidity measurement, and to determine the effect of the concept attainment learning model on the fourth semester student learning outcomes in the Science Education Study Program. This research is a quasi-experimental research. The research design used is a pretest-posttest control group design with purposive sampling technique. From the results of the study, it was found that after the application of the concept attainment learning model, students were more active and enthusiastic. Student learning outcomes after the application of the concept attainment learning model are in the high category, namely 52.95% with an average value of 81.97. It can be concluded that there is an influence of the concept attainment learning model on learning activities and learning outcomes in the fourth semester students of the Science Education Study Program, known from the average value of 81.97 and is included in the high category.